Factors influencing women's perceptions of choice and control during pregnancy and birth: a cross-sectional study - Patricia Leahy-Warren; Helen Mulcahy; Paul Corcoran; Róisín Bradley; Mary O'Connor; Rhona O'Connell (BMC, 2021)
Abstract Background Women across the world value choice and control throughout their maternity care experiences. In response to this health policy and frameworks are adapting and developing. The concepts of choice and control are extrinsically complex and open to interpretation by healthcare professionals and service users, with the two not necessarily aligning. Depending on a number of factors, women's experiences of choice and control within the same maternity care system may be very different. This study aimed to investigate the factors influencing women's perceptions of choice and control during pregnancy and birth in Ireland. Methods We conducted a cross-sectional study using an adapted version of the UK national maternity experience survey (National Perinatal Epidemiology Unit). During March - July 2017, a sample of 1277 women were recruited from the postnatal wards of three maternity units and a tertiary maternity hospital. Poisson regression was used to assess the association between twelve factors and a series of measures of the women's perception of choice and control. Results Most women reported not having choice in the model or location of their maternity care but most reported being involved enough in decision-making, especially during birth. Women who availed of private maternity care reported higher levels of choice and control than those who availed of public maternity care. This factor was the most influential factor on almost all choice and control measures. Conclusion Most women experiencing maternity care in Ireland report not having choice in the model and location of care. These are core elements of the Irish maternity strategy and significant investment will be required if improved choice is to be provided. Availing of private maternity care has the strongest influence on a woman's perceived choice and control but many women cannot afford this type of care, nor may they want this model of care.